An Accountant's Perspective in Assessing Behavioral Accounting in Aspects of Decentralization and Employee Performance Evaluation - Trisnaningsih, Sri; Hanni Fadhillah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to present an in-depth literature review related to the role of accountants in assessing behavioral accounting in the decentralization aspect and evaluating employee performance in organizations. The focus of the research involves understanding accountants' views regarding performance measurement in a decentralized context. This research examines several research articles regarding behavioral accounting in the aspect of decentralization and performance evaluation by collecting data using documentation methods in the form of primary and secondary data. The collected data is then analyzed according to theory to draw a conclusion that shows the research objectives. The results of this research show that Behavioral Accounting is used by companies to measure employee performance but is not widely used for decentralization aspects because there are still many companies that do not place decision-making authority in branch management. Decentralization also has no influence on measuring employee performance or managerial performance. Employee behavior is used more to measure performance which is related to the employee's own incentive assessment.